The feasibility of decreasing the thresholds for biopsy in Kwak and C TIRADSs - Fu, Chao; Cui, Yiyang; Li, Jing; Wang, Yan; Si, Caifeng; Cui, Kefei (Frontiers in Oncology, 2023)
Objectives: To estimate the feasibility of decreasing the original thresholds for biopsy in Kwak Thyroid Imaging Reporting and Data System (Kwak TIRADS) and Chinese Thyroid Imaging Reporting and Data System (C TIRADS). Methods: This retrospective study included 3201 thyroid nodules from 2146 patients with pathological diagnosis. We lowered the original fine-needle aspiration (FNA) thresholds with the TR4a-TR5 in Kwak and C TIRADS and calculated the ratio of additional benign to malignant nodules being biopsied (RABM). If RABM is less than 1, the decreased FNA thresholds could be accepted and used to the modified TIRADSs (modified C and Kwak TIRADS). Then, we estimated and compared the diagnostic performance between modified TIRADS and original TIRADS to determine if the decreased thresholds could be an effective strategy. Results: A total of 1474 (46.0%) thyroid nodules were diagnosed as malignant after thyroidectomy. The TR4c-TR5 in Kwak TIRADS and TR4b-TR5 in C TIRADS had a rational RABM (RABM<1). Modified Kwak TIRADS had higher sensitivity, positive predictive value, negative predictive value and had lower specificity, unnecessary biopsy rate, and missed malignancy rate compared with original Kwak TIRADS (94.1% vs 42.6%, 59.4% vs 44.6%, 89.9% vs 52.8%, 45.0% vs 54.9%, 40.6% vs 55.4%, and 10.1% vs 47.1%, respectively, P < 0.05 for all). Similar trends were seen in modified C TIRADS versus original C TIRADS (95.1% vs 38.7%, 61.7% vs 47.8%, 92.3% vs 55.0%, 49.7% vs 64.0%, 38.3% vs 52.2%, and 7.7% vs 44.9%, respectively, P < 0.05 for all). Conclusions: Biopsy of all nodules with TR4C-TR5 in the Kwak TIRADS and TR4B-TR5 in the C TIRADS might be an effective strategy. This paper contributes to the contradictory concerning whether perform FNA for the nodules smaller than 10 mm.